Peran Revolusi Teknologi Terhadap Budaya Organisasi Dan Interaksi Antar Karyawan Dalam Lingkungan Kerja - Nur Lailatul Hidayah; Putri Ayu Andini; Algitama Wandana Putera; Sutri Anisa; Mochammad Isa Anshori (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research is motivated by the increasing conditions of technological development. Technology has become an important factor in various aspects of human life, one of which is in the world of business and organizations. The development of technological tools can facilitate collaboration between teams to be more efficient, thus impacting the formation of an organization's culture and relationships between employees. The purpose of this study is to analyze the influence of the technological revolution on organizational cultural conditions and the formation of social dynamics between employees in the work environment. Research conducted using the type of writing literature studies or literature review studies that focus on comparing data from several journals or sources through a series of analysis and summarization activities. The research method applied is a qualitative method by containing sources from several previous research journals and e-books published on digital platforms. The results show that the influence of the technological revolution in the formation of organizational culture and interaction between employees can realize team collaboration efficiently and create correlations in a wider scope. However, dependence on technology can lead to social isolation and unnecessary conflict. There needs to be an understanding for every individual and company about the advantages and disadvantages that can result from access to technology. In addition, strategies need to be created to achieve harmony in an increasingly productive work environment.